Deah, Maanyan, and Banjarnese Languages Kinship in Tabalong Regency South of Kalimantan - Akhmad Humaidi; Isna Kasmilawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Tabalong Regency will become one of the supporting cities for the new National Capital because of its strategic location and available resources. The ethnic diversity in Tabalong creates a multilingual situation which gives rise to a number of problems, such as the threat of extinction of minority languages due to the dominant language and socio-political conflicts due to tension due to less effective communication processes. Knowledge about the relationship of language in inter-ethnic interactions can strengthen feelings of inter-ethnic kinship. This research aims to determine the relationship between the main languages in Tabalong, namely Deah, Maanyan and Banjar. The techniques used are lexicostatistics and glotochronology. The results of data analysis using lexicostatistical techniques found that these three languages are classified as families at the linguistic level with a kinship percentage of Deah - Maanyan of 59%, Deah - Banjar of 50%, and Maanyan - Banjar of 52%. Glotochronological analysis shows that the separation time for these three languages, namely Deah - Maanyan is around 1,331-1,101 years, Deah - Banjar is around 1,729-1,463 years, and Maanyan - Banjar is 1,635-1,377 years. The phonemic correspondence of the three languages, namely Deah – Maanyan corresponds to the phonemes /o/ /ε/ and /s/ /h/, Deah – Banjar corresponds to the phonemes /o/ /a/ and /w/ /b/ , and Maanyan – Banjar correspond to the phonemes /ε/ /a/, /ε/ /i/, /h/ /s/, /w/ /b/, and /s/ /c/.